Construction of recombinant Omp25 or EipB protein loaded PLGA nanovaccines for Brucellosis protection - Akmayan, Ilkgul; Oztav, Sedanur; Coksu, Irem; Abamor, Emrah Sefik; Acar, Serap; Ozbek, Tulin (IOP Publishing Ltd, 2024)
Safe and effective vaccine candidates are needed to address the limitations of existing vaccines against Brucellosis, a disease responsible for substantial economic losses in livestock. The present study aimed to encapsulate recombinant Omp25 and EipB proteins, knowledged antigen properties, into PLGA nanoparticles, characterize synthesized nanoparticles with different methods, and assessed their in vitro/in vivo immunostimulatory activities to develop new vaccine candidates. The recombinant Omp25 and EipB proteins produced with recombinant DNA technology were encapsulated into PLGA nanoparticles by double emulsion solvent evaporation technique. The nanoparticles were characterized using FE-SEM, Zeta-sizer, and FT-IR instruments to determine size, morphology, zeta potentials, and polydispersity index values, as well as to analyze functional groups chemically. Additionally, the release profiles and encapsulation efficiencies were assessed using UV-Vis spectroscopy. After loading with recombinant proteins, O-NPs reached sizes of 221.2 +/- 5.21 nm, while E-NPs reached sizes of 274.4 +/- 9.51 nm. The cumulative release rates of the antigens, monitored until the end of day 14, were determined to be 90.39% for O-NPs and 56.1% for E-NPs. Following the assessment of the in vitro cytotoxicity and immunostimulatory effects of both proteins and nanoparticles on the J774 murine macrophage cells, in vivo immunization experiments were conducted using concentrations of 16 mu g ml-1 for each protein. Both free antigens and antigen-containing nanoparticles excessively induced humoral immunity by increasing produced Brucella-specific IgG antibody levels for 3 times in contrast to control. Furthermore, it was also demonstrated that vaccine candidates stimulated Th1-mediated cellular immunity as well since they significantly raised IFN-gamma and IL-12 cytokine levels in murine splenocytes rather than IL-4 following to immunization. Additionally, the vaccine candidates conferred higher than 90% protection from the infection according to challenge results. Our findings reveal that PLGA nanoparticles constructed with the encapsulation of recombinant Omp25 or EipB proteins possess great potential to trigger Brucella-specific humoral and cellular immune response.
Keywords: brucellosis; recombinant antigenic protein; Omp25; EipB; nanovaccine; NANOPARTICLES; ABORTUS; Science & Technology - Other Topics; Materials Science; Physics